2007
DOI: 10.5902/198050981946
|View full text |Cite
|
Sign up to set email alerts
|

Estudo dos constituintes macromoleculares, extrativos voláteis e compostos fenólicos da madeira de candeia – <i>Moquinia polymorpha</i> (Less.) DC.

Abstract: RESUMONeste estudo, foram analisados os principais componentes químicos da madeira da Moquinia polymorpha (LESS.) DC., conhecida como candeia ou cambará, nativa da região Sul de Minas Gerais. A composição química dessa madeira foi: 47,5% de α-celulose, 25,4% de hemiceluloses A e B, 24,0% de lignina, 73,2% de holocelulose, 3,82% de extrativos em etanol:cicloexano (1:1, v v -1 ), 3,21% em etanol e 4,04% em água quente. Nos compostos voláteis identificados, destacaram-se: ABSTRACTIn this study, the main chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
5
0
3
Order By: Relevance
“…Sartori et al (2018) [65] found yields of 360.5 and 401.2 mg EAG/g for the extract in ethanol:water (50% v/v) for the bark of two E. urophylla hybrids. Lima et al (2007) [1] reported a total phenol content of 0.93 mg/g of wood in methanol:water extracts of Candeia (Moquinia polymorpha (LESS.) DC.)…”
Section: Composition Of Wood Extractivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sartori et al (2018) [65] found yields of 360.5 and 401.2 mg EAG/g for the extract in ethanol:water (50% v/v) for the bark of two E. urophylla hybrids. Lima et al (2007) [1] reported a total phenol content of 0.93 mg/g of wood in methanol:water extracts of Candeia (Moquinia polymorpha (LESS.) DC.)…”
Section: Composition Of Wood Extractivesmentioning
confidence: 99%
“…The wood's characteristics vary, depending on genetic and environmental variations, influencing its potential for different uses [1][2][3]. Wood is a biological, heterogeneous, complex material, with variations between species, individuals of the same species and parts of the same individual [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on G. polymorpha subsp. unspecified, reported the isolation of the triterpene bauerenyl acetate and dehydrocostus lactone from the bark and trunk bark (Farias et al, 1984), sesquiterpenes, sesquiterpene lactones and dimeric lactones from the roots and aerial parts (Bohlmann et al, 1986), flavonoids, phenolic compounds and a proline derivative from more polar extracts from leaves (Moreira et al, 2000), and essential oil of the wood (Lima et al, 2007). The studies on G. polymorpha subsp.…”
Section: Introductionmentioning
confidence: 99%
“…A classificação dos extrativos está relacionada, principalmente, com suas características estruturais. Segundo Lima et al (2007) e Esteves et al(2011) esses compostos, normalmente, são formados por ácidos orgânicos, álcoois, aldeídos, ésteres, cetona, fenóis de baixa massa molecular, hidrocarboneto alifáticos e terpenos. Dependendo da polaridade do solvente utilizado, pode-se obter determinada classe de extrativos da madeira, seja apolar ou polar.…”
Section: Introductionunclassified